Aplikasi Pengenalan Nama Surah pada Juz ke 30 Kitab Suci Al-Qur’an Menggunakan Speech Recognition - Dhimas Sena Rahmantara; Kartina Diah Kesuma Wardhani; Maksum Ro’is Adin Saf (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Al-Qur’an is a scripture which contains the saying of Allah Subhanahu Wa Ta’aala and was revealed to Prophet Muhammad. The 30th juz is the juz that exists in the Al-Qur’an. When studying how to read Al-Qur’an well, the first thing that is learned is reading and memorizing surahs in the 30th juz. Nevertheless, there is a problem in remembering or knowing the surah name and the verse which are in the 30th juz. An android application was developed in order to recognize the surah names in the 30th juz by utilizing speech recognition technology to overcome that problem. Markov Model (Markov Chain) algorithm was implemented in this application. This algorithm will process user’s speech and compute probability of the surah name that was spoken. Speech detection testing gave result that the highest accuracy of application in recognizing the speeches was in the environment without noise with the accuracy of 100% in the most ideal distance is 50 cm for male and for female user. Based on the blackbox testing result, all functionalities of the application have functionated well. Control flow testing gave result that the value is 7 which indicates that the code is simple and well written. 87,74% respondents answered, by filling up the questionnaires, that the application is useful in order to make user knows better about the surah names in the 30th juz.